The Role of the State Budget in Realizing Public Welfare through Optimizing State Spending - Jihan Fatin; Usfa Zahara; Zulhamdi Zulhamdi (Al-Hiwalah: Journal of Sharia Economic Law, 2025)
The State Budget (APBN) is the primary instrument used by the Indonesian government to manage state finances and achieve national development goals. APBN management reflects the state's commitment to realizing public welfare through targeted resource allocation. This article aims to examine various types of state expenditure within the APBN structure, including personnel expenditure, goods expenditure, capital expenditure, debt interest payments, subsidies, grants, social assistance, other expenditures, and transfers to regions. Using a descriptive-analytical approach, this article discusses the role and function of each type of expenditure in supporting national development and public services. Understanding the structure of state expenditure is expected to contribute to the evaluation of fiscal policy and the strengthening of state financial governance. The conclusion of this study confirms that optimizing state expenditure allocation is key to achieving inclusive and sustainable development.